2011
DOI: 10.1080/01635581.2011.607548
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Induces Apoptosis of Cisplatin-Resistant Stomach Cancer Cells by Causing Degradation of Cisplatin-Inducible Aurora-A Protein

Abstract: Various chemotherapeutic agents such as cisplatin have been used to treat gastric cancer. However, a substantial number of patients acquire resistance to this treatment, and this is followed by rapid relapse of the disease. We investigated the anticancer effect of capsaicin, the active ingredient in red pepper, in the cisplatin-resistant Korean human gastric cancer cell line SNU-668. We found that treatment of SNU-668 cells with capsaicin in combination with cisplatin induced higher apoptotic cell death than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Except aforementioned therapeutic value, several studies also have demonstrated that capsaicin could be functioned as a chemopreventive and chemotherapeutic agent in different human cancer models. As reported, capsaicin decreased the growth of human leukemic cells 6, gastric 7, nasopharyngeal 8, prostate 9, and hepatic carcinoma cells 10 in vitro because of its ability to mediate cell cycle arrest and induce cell apoptosis. However, the molecular mechanism underlying capsaicin-induced growth inhibition and apoptosis was not exhaustively elucidated.…”
Section: Introductionmentioning
confidence: 60%
“…Except aforementioned therapeutic value, several studies also have demonstrated that capsaicin could be functioned as a chemopreventive and chemotherapeutic agent in different human cancer models. As reported, capsaicin decreased the growth of human leukemic cells 6, gastric 7, nasopharyngeal 8, prostate 9, and hepatic carcinoma cells 10 in vitro because of its ability to mediate cell cycle arrest and induce cell apoptosis. However, the molecular mechanism underlying capsaicin-induced growth inhibition and apoptosis was not exhaustively elucidated.…”
Section: Introductionmentioning
confidence: 60%
“…In human gastric cell lines, capsaicin induces cell death via bcl-2-sensitive apoptotic pathway [104], overexpression of p53 and/or c-myc genes [107], activation of caspase-3 [108], and inhibits cell proliferation by cytochrome c release [105]. Moreover, capsaicin enhances the potential effectiveness of other chemotherapeutic agents on Korean human gastric cancer cell line, increasing apoptotic cell death of cisplatin-resistant gastric cancer cells after co-treatment with cisplatin [109]. In human colorectal cancer cells in vitro, capsaicin suppressed cell proliferation involving the suppression of transcriptional activity of β-catenin [106].…”
Section: Chemopreventive Activitymentioning
confidence: 99%
“…Monofunctional platinum-based drugs, like LH5, showed increased apoptotic activity in combination with capsaicin [10]. Similarly, the treatment of stomach cancer cells with a combination of cisplatin and capsaicin caused greater than apoptosis than either of these agents given singly [11, 12]. A similar effect was also observed when capsaicin was given in combination with the doxorubicin analog pirarubicin [13].…”
Section: Introductionmentioning
confidence: 99%